Animal Models of Non-Respiratory, Post-Acute Sequelae of COVID-19 - Abigail Vanderheiden; Michael S. Diamond (Viruses)
Post-acute sequelae of COVID-19 (PASC) are a diverse set of symptoms and syndromes driven by dysfunction of multiple organ systems that can persist for years and negatively impact the quality of life for millions of individuals. We currently lack specific therapeutics for patients with PASC, due in part to an incomplete understanding of its pathogenesis, especially for non-pulmonary sequelae. Here, we discuss three animal models that have been utilized to investigate PASC: non-human primates (NHPs), hamsters, and mice. We focus on neurological, gastrointestinal, and cardiovascular PASC and highlight advances in mechanistic insight that have been made using these animal models, as well as discussing the sequelae that warrant continued and intensive research.